Self-Assembly M2e-Based Peptide Nanovaccine Confers Broad Protection Against Influenza Viruses - Wang, Qimin; Zhang, Yuling; Zou, Peng; Wang, Meixiang; Fu, Weihui; She, Jialei; Song, Zhigang; Xu, Jianqing; Huang, Jinghe; Wu, Fan (Frontiers in Microbiology, 2020)
The extracellular domain of influenza M2 protein (M2e) is highly conserved and is a promising target for development of universal influenza vaccines. Here, we synthesized a peptide vaccine consisting of M2e epitope linked to a fibrillizing peptide, which could self-assemble into nanoparticle in physiological salt solutions. When administrated into mice without additional adjuvant, the influenza A M2e epitope-bearing nanoparticles induced antibodies against M2e of different influenza subtypes. Comparing with other M2e-based vaccine, these M2e nanoparticles did not induce immune response against the fibrillizing peptide, demonstrating minimal immunogenicity of vaccine carrier. Furthermore, vaccination with M2e-based nanoparticles did not only protect mice against homologous challenge of influenza PR8 H1N1 virus, but also provide protection against heterologous challenge of highly pathogenic avian influenza H7N9 virus. These results indicated that M2e-based self-assembled nanoparticle vaccine is safe and can elicit cross-protection, therefore is a promising candidate of universal influenza vaccines.